Natureza do serviço social em Angola: gênese, formação, concepções e prática profissional dos assistentes sociais nos serviços de saúde das forças armadas angolanas - Monteiro, Amor António (2016)
This work aims to discuss the nature of social work in Angola in general and particularly in the Angolan Armed Forces Health Services. Based on Marx's theoretical framework and the authors linked to it, we assume that to grasp the nature of social work in Angola requires identifying in what is temporary, phenomenal, immediate, occurs in everyday life, that is, in its genesis, in the training process of its agents and in their concepts and professional practice, what is conserved in the continuity of the historical process. The field research shows that the nature of social work in Angola is marked by being a profession, that is, a specialized work in the context of socio-technical labour division permeated by the characteristics of the professionals, for their views on the profession, the nature of everyday work practice, the socio-historical context that demanded its creation, re-creation and gives meaning to it, by the demands and interests of the institutions that hire a social worker, and also by the demands and interests of the individuals to whom the service of social workers is delivered